PEMBERDAYAAN KARANG TARUNA MELALUI PELATIHAN PEMBUATAN LOGO GRAVIR DAN EMBOSS MENGGUNAKAN COMPUTER NUMERICAL CONTROL (CNC) - Halim Mahfud; Donny Montreano; Nur Cholis; Reda Rizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The authenticity or validity of a document issued by an institution or individual is determined by several things such as the signature or wet stamp of the organization's logo. But over time, technology has advanced so much that signatures and wet stamps can be copied without permission. One way to maintain the authenticity of paper documents is with an embossing tool. This tool will be made using CNC for the administrative needs of the Karang Taruna organization (katar) in Cilobak, Pondok Labu. Katar members were trained to use CNC for embossing and engraving tools. The engraving was used to produce the identity nameplate that is put on the chest and the logo on the work desk. In addition, engraving was used to carve award plaques or commemorative plaques from katar to its guests or other ceremonial events. This training was print skilled katar in the production process of paper embossing tools and board production with engraving techniques, it is expected to be a pioneer for businesses in the field of CNC services among the katar members.